1998
DOI: 10.1046/j.0909-8836.1998.eos106402.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental anxiety among 18‐yr‐olds in Norway, Prevalence and related factors

Abstract: The aims of this study were to determine the prevalence of dental anxiety at the time when adolescents are leaving the public dental service, and to explore the relationship at this stage between dental anxiety and some possible etiologic factors. The sample consisted of 571 18-yr-olds in high school who completed a questionnaire and three psychometric scales, the Dental Fear Scale (DFS), the Dental Beliefs Survey (DBS) and the Geer Fear Scale (GFS), in the classroom. The relationship between dental anxiety (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
94
6
22

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(139 citation statements)
references
References 0 publications
17
94
6
22
Order By: Relevance
“…We did not find any comparable results from other studies of medical and dental students; a similar association between education and DA was found among adults in Iceland [12], while differences in DA according to parents’ education level were not statistically significant in 18-year-old Norwegian students [38]. More educated parents, characterised by high SES and less oral health problems, may maintain a positive attitude towards dentists and dental treatment indirectly, through their own experience [7].…”
Section: Discussioncontrasting
confidence: 78%
“…We did not find any comparable results from other studies of medical and dental students; a similar association between education and DA was found among adults in Iceland [12], while differences in DA according to parents’ education level were not statistically significant in 18-year-old Norwegian students [38]. More educated parents, characterised by high SES and less oral health problems, may maintain a positive attitude towards dentists and dental treatment indirectly, through their own experience [7].…”
Section: Discussioncontrasting
confidence: 78%
“…A large array of studies on dental anxiety suggests that the experience of pain is one of the most powerful conditioning experience in terms of the development of dental phobia (see, for example, Davey, 1989;Liddell & Gosse, 1998;Locker et al, 1996;Skaret et al, 1998;Vassend, 1993). Among the wide variety of dental experiences potentially predisposing to pathological forms of dental anxiety investigated in the present study, including pain, the retrospective report of helplessness during treatment was found to be most Table 3 Final results of the stepwise logistic regression analysis in the analysis of 'high dental anxiety' (1 = yes, 0 = no) and 'fulfilling criteria for dental phobia' (1 = yes, 0 = no).…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of the first category involve (a) invasive dental treatments, for instance, root canal treatments or injections (see, for example, Abrahamsson et al, 2002;Berggren & Meynert, 1984;Davey, 1989;Liddell & Gosse, 1998;Locker, Shapiro, & Liddell, 1996;Moore et al, 1991;Stouthard, Rijkse, & Van den Berg, 1992;Vassend, 1993); (b) pain (see, for example, Abrahamsson et al, 2002;Berggren & Meynert, 1984;Davey, 1989;De Jongh et al, 1995;De Jongh, van der Burg, van Overmeir, Aartman, & van Zuuren, 2002;Skaret, Raadal, Berg, & Kvale, 1998;Versloot, Veerkamp, & Hoogstraten, 2008); (c) distress caused by dentist behavior (see, for example, Abrahamsson et al, 2002;Stouthard et al, 1992); (d) distressing emotional responses to dental treatment (for example, feelings of helplessness or loss of control; see De Jongh et al, 2002Moore, Brodsgaard, & Rosenberg, 2004); and (e) distressing stories told by important others (Abrahamsson, Berggren, & Carlsson, 2000;Moore et al, 1991). Examples of traumatic stressors reported by subjects with pathological forms of dental anxiety are (a) sexual abuse (see, for example, Leeners et al, 2007;Walker, Milgrom, Weinstein, Getz, & Richardson, 1996;Willumsen, 2004); (b) war trauma (Friedlander, Mills, & Wittlin, 1987); (c) severe traffic accidents (Smyth, 1999); (d) a tragic death of a loved one (Berggren, 1992); (d) a distressing medical experience (Lautch, 1971); and (e) physical assault (De Jongh et al, 2006;Walker et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Since any bias from overestimation or underestimation of dental anxiety would affect both groups, it is unlikely that the results were flawed. The reported prevalence of dental anxiety in Scandinavian teenagers varies between 3% and 19% [11,12]. The difference might be explained by different populations with different caries experience being investigated and/or by different methods used for assessing dental anxiety.…”
Section: Discussionmentioning
confidence: 99%